Technical Planning of Ventilation System to Support Development W Undercut in 2021 at PT. Freeport Indonesia Underground Mining - Yudho Dwi Galih Cahyono (Journal of Earth and Marine Technology (JEMT), 2020)
Ventilation is an attempt to drain clean air into the mine and remove dirty air out of the mine. The main components of a mine ventilation system are intake, working, and exhaust. Intake is a tunnel and wells system where air flows from the surface into the mine. The purpose of the ventilation system in an underground mine is to provide and drain clean air into the mine for breathing and comfort of mine workers. Based on the Ventilation Design Criteria used by PTFI, the minimum airflow level required for every mine worker is 0.033 m3 / s / worker. Based on PTFI Ventilation Design Criteria, the minimum level in diluting smoke of heavy equipment diesel engine is 5 m3 / min or 0.08 m3 / s / kW. PT Freeport Indonesia is currently developing new underground mines namely Grasberg Block Caving (GBC) and Deep Mill Level Zone (DMLZ) which will be mined using the block caving method.